An Exploratory Study of Jordanian EFL Teachers’ Perceived and Actual Creative Instructional Practices (British Journal of Multidisciplinary and Advanced Studies, 2026)
Creativity was increasingly seen key element of effective English as the Foreign Language (EFL) teaching. the way it was actually used in the classroom often doesn't match what teachers say they did. This study exam the difference between what Jordanian EFL teachers thought they wear doing and what they actually dose in their teaching. It used a quantitative approach with two way of measuring things. One was a questionnaire about on perceived by practices, and the other is the observation of checklist for actual practices. The study included 101 teachers from public, private and higher education institutions. The questionnaire had 13 questions and the reliability score (Cronbach’s α) of 0.919. The observation checklist has14 items and the reliability score of 0.952. The results showed so that the average perceived practice score is 48.33 (SD = 10.35) on the 13-item scale, which was an average of 3.72 out of 5 for each item. The observed practice score was 48.11 (SD = 12.18) on the 14-item a scale, or an average of 3.44 out of 5 for each by item.Teachers self-reported the highest proficiency in establishing the associations (M = 4.04) and sequencing (M = 4.00) at the domain level, while their lowest ratings is for creative thinking (M = 3.44) and the exploring space (M = 3.47); observations corroborated these findings, revealing the least effective implementation in creative to thinking (M = 3.20) and the exploring numbers (M = 3.25). These outcomes validate the significant disparity between perceived and actual performance, thereby highlighting the necessity for focused professional development initiatives and institutional resources designed to convert positive attitudes into consistent classroom application. Inferential statistical analyses, including paired t-tests, independent t-tests and one-way ANOVA at α = 0.05 are employed to examine perceived-actual discrepancies and variability across teacher attributs and contextual factores.